Exploring Mathematical Concepts in Pèsapèyan Ling-Giling: A Traditional Game as Miniature of Bull Racing in Madura Island - Rosikhoh, Dewi; Rofiqi, Rofiqi; Arjuna, Mohammad (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2025)
Pèsapèyan ling-giling was one of the iconic local wisdom of Madura. This game was a miniature version of the bull race. In this game, wheels replaced the bull as the driving force. As a result, this game was suitable for players of all ages. This research aimed to explore mathematical concepts in the pèsapèyan ling-giling game. This research used a qualitative approach with an ethnographic research type. Researchers used taxonomic analysis to examine the internal structure of mathematical concepts within the stages of the pèsapèyan ling-giling game. The study showed that the pèsapèyan ling-giling game contained mathematical concepts in the stage of tool-making, game rules, gameplay, and playing field. The mathematical concepts found in pèsapèyan ling-giling were numbers (e.g. the concepts of order, ranking, estimation, and optimization), measurement (e.g. the concept of length, area, speed, and distance, geometry (e.g. the concepts of lines, rectangles, circles, blocks, symmetry, coordinates, and position), discrete mathematics (e.g. the concept of graphs, relations and functions, and combinatorics) proportion, and probability. Thus, the traditional game of pèsapèyan ling-giling could be a learning medium for these mathematical concepts at elementary and secondary schools.